The prevalence and pathology of ovine coccidiosis in kerman, iran - Reza Kheirandish; Saeid R Nourollahi-Fard; Elham Eslah (Eurasian Journal of Veterinary Sciences)
Aim: This study was undertaken to determine Eimeria infection in sheep in Kerman province. Material and Methods: Totally 227 faecal samples were collected directly from the rectum of sheep. Faecal samples were analyzed using floatation technique for the presence of coccidian oocysts. Oocysts per gram of feces and Eimeria species were identified. Results: Seven species of Eimeria (E. crandallis, E. ovina, E. parva, E. ovinoidalis, E. faurei, E. ahsata and E. intricata) were identified. The age and sex of the sheep had no significant (p>0.05) effects on prevalence of coccidiosis. Conclusion: Eimeria infection was prevalent in sheep and anticoccidial treatments should be recommended.